A Decade of Varicella Screening Within a Paediatric Inflammatory Bowel Disease Population. (31st December 2019) - Harris, Rachel E; Curtis, Lee; Hegde, Vikas; Garrick, Vikki; Gervais, Lisa; Armstrong, Lawrence; Delahunty, Caroline; Eccleston, Andrew; Al-Hourani, Ghassan; Flynn, Diana M; Merrick, Victoria; Barclay, Andrew R; et al.
Abstract: Introduction: Increased risk of opportunistic infection—e.g., varicella zoster infection—secondary to therapies is a cause of morbidity in inflammatory bowel disease [IBD] patients. The UK vaccination schedule does not include varicella immunisation. We aimed to evaluate the varicella screening and immunisation programme in a paediatric IBD population. Methods: Data regarding IBD diagnosis, varicella status, and consequent immunisations/treatment interventions were collected retrospectively from the records of patients diagnosed with IBD over a 10-year period [2009–2018]. Results: In all, 520 IBD patients were diagnosed; 505/520 [97%] had varicella testing; 46/505 [9%] were naïve. Of 501 patients, 391[78%] were tested before or within 7 days of diagnosis; this increased in the second 5-year period compared with the first (229/268 [85%] versus 162/233 [70%]; p <0.00001). Median diagnosis age of naïve patients was lower [8.3 years versus 12.8 years; p <0.00001]. Where vaccination was feasible, 21/31 [68%] had two and 7/31 [23%] one immunisation. Prednisolone induction led to lower rates of vaccination (5/13 [39%] versus 23/33 [70%] for other induction therapies; p =0.02). Of 28 vaccinated patients, 5 [18%] had suspected breakthrough varicella; and 6/18 [33%] unimmunised patients required post-exposure prophylaxis or treatment for varicella. Immunisation was associated with a decrease in patients requiring post-exposure prophylaxis (0/28 [0%] versus 5/18 [28%]; p =0.0006) and varicella-related hospital admission (1/28 [4%] versus 4/18 [22%]; p =0.01). Conclusions: High rates of varicella screening and immunisation within a PIBD population are possible, resulting in a reduction in hospital admissions for varicella treatment. Varicella immunisation may be of increasing importance within the PIBD population with the emergence of novel therapeutic strategies.